Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0170
|View full text |Cite
|
Sign up to set email alerts
|

Best Value Procurement – Experiences From the Execution Phase

Abstract: Best value procurement (BVP) is one of the approaches for early contractor involvement (ECI) in public construction projects. Despite an increased number of projects using the approach, there is a lack of knowledge regarding use of BVP in the Norwegian construction industry. Little research has been done on the consequences due to BVP, and the approach is often misinterpreted as only a procurement model. However, BVP provides an important mind-set for all parties involved, also during the execution phase. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Furthermore, the cross-sectional exploration (considering all stages of the procurement process referred to in the procurement file) of the social pillar of public procurement carried out in this study complements previous literature focusing on the study of particular stages, especially the second stage (supplier selection) (e.g., Akenroye, 2013;Bergman & Lundberg, 2013;Falagario et al, 2012;Lindholm et al, 2019;Watt et al, 2009); the third stage (contract execution) remains understudied (Nygård et al, 2019) despite the importance of this final stage in the public procurement process, as it is here where the indicators that have been designed in earlier stages of the public procurement process should be implemented (Nygård et al, 2019). Moreover, the literature that has explored the social pillar of public procurement mainly relies on the use of questionnaires (Akenroye, 2013;Brammer and Walker, 2011;Chiarini et al, 2017;Prier et al, 2016), and to a lesser extent, interviews (Holma et al, 2020;Selviaridis et al, 2011).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the cross-sectional exploration (considering all stages of the procurement process referred to in the procurement file) of the social pillar of public procurement carried out in this study complements previous literature focusing on the study of particular stages, especially the second stage (supplier selection) (e.g., Akenroye, 2013;Bergman & Lundberg, 2013;Falagario et al, 2012;Lindholm et al, 2019;Watt et al, 2009); the third stage (contract execution) remains understudied (Nygård et al, 2019) despite the importance of this final stage in the public procurement process, as it is here where the indicators that have been designed in earlier stages of the public procurement process should be implemented (Nygård et al, 2019). Moreover, the literature that has explored the social pillar of public procurement mainly relies on the use of questionnaires (Akenroye, 2013;Brammer and Walker, 2011;Chiarini et al, 2017;Prier et al, 2016), and to a lesser extent, interviews (Holma et al, 2020;Selviaridis et al, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…Stage 3 is the actual execution of the contract by the supplier selected in the previous stage (Nygård et al, 2019;Racca et al, 2011). Public entities must always make sure that, notwithstanding any unforeseen events that may arise by chance, the contract is fulfilled as stipulated (Fox & Morris, 2015;Racca et al, 2011).…”
Section: Public Procurement As a Processmentioning
confidence: 99%
“…This procurement method attempts to choose the best AEC team based on what the client considers to add value to the project rather than the low price of the proposals (Ying et al, 2021). Moreover, BV procurement allows for the early involvement of the contractor in a public construction project (Nygård et al, 2019). The procurement method has commonly been used to minimize the involvement of the client during the design and execution phases of the project since the contractor is considered the expert and the only member capable of making decisions related to the development of the construction project (Wondimu et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The procurement method has commonly been used to minimize the involvement of the client during the design and execution phases of the project since the contractor is considered the expert and the only member capable of making decisions related to the development of the construction project (Wondimu et al, 2018). Multiple studies have reported (Lesjø et al, 2019;Nygård et al, 2019;Tillmann et al, 2017;Whelton et al, 2004;Wondimu et al, 2018) that, even though BV focuses on ensuring both value and lower costs before construction starts, there is still conflict and misalignment between the owner and the contractor about these aspects during the execution phase of the project. Furthermore, misalignments of commercial incentives in AEC projects can be avoided if participants select trusted and competent members; business models and key performance metrics is communicated well; stick around to adapt towards the principles of IPD and TVD; ensure that participants are adequately trained in lean construction; and adequate resources to implement IPD and TVD systems (Do et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation